Nipah Frond Waste as a Renewable Source for Carboxymethyl Cellulose (International Journal of Scientific Research in Science and Technology, 2024)
Nipah frond is one of the wastes that has not been widely utilized by community. Nipah frond contain a relatively high cellulose content that can be used as renewable source for carboxymethyl cellulose production. This research focus on the extraction of cellulose from nipah fronds, followed by synthesis of carboxymethyl cellulose through alkalization and carboxymethylation processes. In the process of the synthesis carboxymethyl cellulose, cellulose was carried out by alkalization and carboxymethylation using sodium hydroxie (NaOH), and trichloroacetic acid. Characterization of carboxymethyl cellulose (CMC) was carried out by Fourier Transform Infrared (FTIR). The degree of substitution (DS) was determined using the rasio of -OH and ether absorption. The effect of various concentrations of trichloroacetic acid on the DS of CMC was analyzed. DS of CMC obtained through variations in trichloroacetic acid concentration shows a decreasing trend in DS value due to the formation of by-product that inhibit the carboxymethylation. The maximum DS of 0.92 was obtained when the carboxymethylation process with 15% of trichloroacetic acid. The result of the analysis using FT-IR spectrophotometer showed there is a stretching O-H group at the wave number of 3333 cm-1, and supported with the ether vibration in the 1024 cm-1 and the presence of the carbonyl group COO- at 1601 cm-1.